Remembering old partnerships: Networking as new medical schools within BoLeSwa countries - L Badlangana; K Matlhagela; N Tlale (South African Medical Association, 2016)
In southern Africa, former members of the Botswana-Lesotho-Swaziland (BoLeSwa) partnership, Botswana and Lesotho, have established their first and onlyÂ publicly funded medical schools in their countries. Swaziland has a private medical school. The three countries have a long history of partnership throughthe University of Botswana, Lesotho and Swaziland (UBLS) system âˆ' a derivative of BoLeSwa. Botswana and Lesotho are also members of a newly foundedÂ Consortium of New Southern African Medical Schools (CONSAMS). The UBLS was established in Lesotho in 1964 by a royal charter, two years before theÂ three countries gained independence. It was founded to address manpower constraints in anticipation of their independence. The three countries had agreedto concentrate on different professional trainings, as follows: Botswana in engineering, Swaziland in agriculture, and Lesotho in medicine. CONSAMS wasestablished as a unique collaborative approach involving south-south networks, which included south-north partnerships. This created an opportunity tostrengthen medical education in the region. The BoLeSwa partnership is further strengthened by participation in CONSAMS by two of the five foundingÂ members. Other members include Mozambique, Namibia and Zambia. A sharing of resources through regional and international partnerships has beenestablished. The sub-Saharan African Medical School Study has examined the challenges, innovations, and emerging trends in medical education in the regionand has made recommendations on how to better share resources. CONSAMS is one innovative way of addressing these issues. Partnerships between theBoLeSwa countries have been strengthened through CONSAMS. This has afforded the new medical schools sharing of their limited resources.